México: Estado y clase dominante - Martínez Escamilla, Ramón (1978)
This article was scanned by the Aurelio Espinosa Polit Ecuadorian Library.With marked frequency are expressed in the publications of dissident and leftist groups, and in the so-called marginal press and even in those of not a few specialized bodies in the social disciplines that are taught or researched in Mexican centers of higher culture, criteria regarding the official conceptions about the general lines in which the public life of Mexico is manifested; and that do not manage to penetrate deeply into the real sense of the political process, generally remaining in the simplistic, emotional, almost religious but openly execrable statement of the facts in which such process takes shape.